2022
DOI: 10.3389/fnana.2022.902218
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Effects of Estrogens and Androgens on Estrogen and Androgen Receptor Expression in Pituitary and Adrenal Glands in Adult Male and Female Rats

Abstract: Sex steroid hormones, such as androgens and estrogens, are known to exert organizational action at perinatal periods and activational effects during adulthood on the brain and peripheral tissues. These organizational effects are essential for the establishment of biological axes responsible for regulating behaviors, such as reproduction, stress, and emotional responses. Estradiol (E2), testosterone, and their metabolites exert their biological action through genomic and non-genomic mechanisms, bounding to cano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…There are poor number of studies, including ours, reported regulatory roles and/or mutual interactions of adrenal estrogen signaling through both canonical and noncanonical estrogen receptors for males (Lagunas et al, 2022; Pacwa et al, 2018; Pawlicki et al, 2023; Trejter et al, 2015). Pharmacological blockage of androgen and GPER estrogen signaling leads to permanent modifications of the neuroendocrine functions of the pituitary and adrenal glands in the adulthood of both sexes (Lagunas et al, 2022). Also, membrane sex receptor signaling is sensitive to environmental androgen and estrogen‐like compounds which nowadays pollute water, land, and air environments (Amir et al, 2021).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…There are poor number of studies, including ours, reported regulatory roles and/or mutual interactions of adrenal estrogen signaling through both canonical and noncanonical estrogen receptors for males (Lagunas et al, 2022; Pacwa et al, 2018; Pawlicki et al, 2023; Trejter et al, 2015). Pharmacological blockage of androgen and GPER estrogen signaling leads to permanent modifications of the neuroendocrine functions of the pituitary and adrenal glands in the adulthood of both sexes (Lagunas et al, 2022). Also, membrane sex receptor signaling is sensitive to environmental androgen and estrogen‐like compounds which nowadays pollute water, land, and air environments (Amir et al, 2021).…”
Section: Discussionmentioning
confidence: 87%
“…In feminizing adrenal tumors, the mechanism of estrogen production has been proposed to be due to either peripheral aromatization of androgens or estrogen production from the tumor itself (Phornphutkul et al, 2001). There are poor number of studies, including ours, reported regulatory roles and/or mutual interactions of adrenal estrogen signaling through both canonical and noncanonical estrogen receptors for males (Lagunas et al, 2022;Pacwa et al, 2018;Pawlicki et al, 2023;Trejter et al, 2015). Pharmacological blockage of androgen and GPER estrogen signaling leads to permanent modifications of the neuroendocrine functions of the pituitary and adrenal glands in the adulthood of both sexes (Lagunas et al, 2022).…”
Section: Discussionmentioning
confidence: 90%
“…Whether estrogen-mediated aldosterone synthesis through ERβ is reconciled with the fact that healthy premenopausal women have higher serum aldosterone levels compared to healthy men of the same age through GPER activity, cannot be assured. It has been described, that in the adrenal glands, unlike the pituitary, GPER expression is not sexually dysmorphic [ 41 , 43 ].…”
Section: Molecular Evidence Of Estrogens In the Biosynthesis Of Aldos...mentioning
confidence: 99%
“…Mainstream of research on the endocrine disrupting chemicals (EDCs) has been reproductive toxicity, which is about the adverse effects of sex steroid-like substances on the hypothalamic-pituitary-gonadal (HPG) hormone axis and its target organs ( Czarnywojtek et al, 2023 ). Since mammalian adrenal glands have steroid receptors, and share a high similarity with gonads in synthesize and secrete steroid hormones from cholesterol, the glands could be suitable for research on EDCs ( Hinson & Raven, 2006 ; Lagunas et al, 2022 ). In fact, EDC studies on the adrenal gland have been gradually accumulating, although in much smaller amounts than on the gonads; these are including adrenal steroidogenesis disruption by diethylstilbestrol (DES) ( Haeno et al, 2015 ), genistein-induced histomorphometric and hormone secreting changes in the adrenal cortex ( Ajdžanović et al, 2009 ), corticosterone secretion changes by low-dose bisphenol-A ( Lan et al, 2015 ), reduced pubertal development of cortex by triphenyltin chloride ( Li et al, 2020 ), and disruption of cortical function by dipentyl phthalate ( Chen et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%